Electrochemical β‐Selective Hydrocarboxylation of Styrene Using CO2 and Water. Issue 3 (17th December 2019) - Kim, Younghye; Park, Gyeong Do; Balamurugan, Mani; Seo, Jiwon; Min, Byoung Koun; Nam, Ki Tae
Abstract: The carboxylation of hydrocarbons using CO2 as a one‐carbon building block is an attractive route for the synthesis of carboxylic acids and their derivatives. Until now, chemical carboxylation catalyzed by organometallic nucleophiles and reductants has been generally adopted particularly for the precise selectivity control of carboxylation sites. As another approach, electrochemical carboxylation has been attempted but these carboxylation reactions are limited to only a few pathways. In the case of styrene, dicarboxylation at the α‐ and β‐positions is mostly observed with electrochemical carboxylation while site‐selective hydrocarboxylations are hardly achieved. In this study, electrochemical β‐selective hydrocarboxylation of styrene using CO2 and water is developed, in which the site selectivity can be precisely controlled between β‐hydrocarboxylation and dicarboxylation without the aid of homogeneous catalysts. In this platform, water is used as proton source in the β‐hydrocarboxylation of styrene where its addition results in significant enhancement of the selectivity toward β‐hydrocarboxylation. This work provides insights into new strategies for site‐selectivity‐controllable carboxylation with CO2 using an electrochemical platform. Abstract : The carboxylation of styrene on a heterogeneously catalyzed electrochemical platform is newly demonstrated, where CO2 and water are used as carbon and proton sources, respectively. The site‐selectivity of carboxylation can be precisely controlled between dicarboxylation and β‐selective hydrocarboxylation solely by providing optimal proton source in the absence of homogeneous catalysts.